A Hubungan Durasi Dan Postur Kerja Penggunaan Komputer Dengan Keluhan Nyeri Leher (Neck Pain) pada Pegawai Kantor Bupati Kampar - Nurlina, Nurlina; Isnaeni, Lira Mufti Azzahri; Lestari, Rizki Rahmawati (KOLONI, 2025)
Someone who works for a long time and work positions that are not ergonomic can certainly cause musculoskeletal disorders. One of the musculoskeletal disorders (MSDs) associated with computer use is neck pain. The cause of neck pain is due to not paying attention to ergonomic positions, resulting in neck muscle fatigue caused by awkward postures of the neck muscles for a long time. The purpose of this study was to determine the relationship between duration and work posture of computer use with neck pain complaints in Kampar Regent Office employees. This type of research is an observational analytic quantitative method with a cross sectional design. The population and sample in this study amounted to 72 people with total sampling technique. Data collection tools using questionnaire distribution and observation. This study uses univariate and bivariate analysis with the fisher exact. The results showed that the duration of work had a p-value of 0.02 (p<0.05), and the work posture had a p-value of 0.04 (p<0.05). This shows that there is a significant relationship between work duration and work posture with neck pain complaints in Kampar Regent Office employees. It is expected that employees of the Kampar Regent's Office pay more attention to the duration and good work posture so as to reduce complaints of neck pain.